MOTIVATION MODEL DISTORTION OF RAMAYANA BALLET PERFORMERS - Mamik Suharti; Cahyani Tunggal Sari; Sulihanto Sulihanto (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2020)
This study reviews the conventional setting of Herzberg Two-Factors Theory and compare with research findings in the Ramayana Ballet show. This research is was done by observation and interview process. This study is a qualitative research that combines historical methods and economics research background. The hygiene factors consist of salary, company policy, good interpersonal relationship and quality of supervision, job security, working condition, and work life balance. The motivation factors consist of personal status, challenging, promotion, responsibility, and growth. This study shows that almost all art groups of Ramayana ballet have high hygiene factor and low motivation. but this findings still led to the high engagement of the artists towards Ramayana ballet show and it was proven by the existence of the art group and the Ramayana ballet show. Implementation of Two Factor Theory Herzberg in the arts group shows different with the factors that have been formed by Herzberg. The artists’ engagement from the art group Ramayana Ballet shows different characteristics.